Self-Regulated Learning In Mathematics Learning: Design of Learning Model Based on Bibliometric Analysis - M.J. Dewiyani Sunarto; Edo Yonatan Koentjoro (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Self-Regulated Learning (SRL) has been a growing topic since 1983 in the Scopus database. The importance of SRL has been known through several studies because it is proven to be able to improve student learning outcomes, both at school and in life. The purpose of this study is to determine the trend of topics in the field, through bibliometric analysis with the help of the VOSViewer application. Findings reveal that there is still little discussion on the topic of SLR in mathematics learning. The journal that can be used as a reference is the International Journal of Science and Mathematics Education, which the latest topics related to Learning Systems and Education. Suggestions for further research are to make technology-based learning models using the latest theories and research results and evaluate the results achieved for improving students’ learning outcomes in mathematics and in life.